Educational results of future teachers in the field of education and their means of their assessment - Tatyana K. Belyaeva; Svetlana V. Frolova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2022)
The paper analyzes the phenomenon of educational outcome in the field of educational activities and the basis for its design. Determining the quality of professional training of a future teacher in the field of educational activities is directly related to a reliable and optimal determination of the level of achievement of a students educational results, since a timely assessment of the level of educational results allows you to create a flexible system for responding to deficit areas in a students education, on the basis of which effective and personalized management takes place. content of education. The purpose of the article is a theoretical analysis, definition and substantiation of the content and composition of the educational results of future teachers in the field of educational activities and evaluative means of achieving them. Methods for researching a scientific problem are theoretical analysis of scientific literature in the field of pedagogy and psychology, methods for designing analysis, systematization and generalization of scientific literature on the research problem. The authors consider the content of the concept of educational result through the integration of competence and labor actions based on the methodological unity of competence-based and activity-based approaches. The paper reveals the content of the educational results of future teachers developed by the authors in the field of educational activities and indicators of their achievement. The authors analyze the means of assessing educational results and the structure of their construction. Test tasks and case tasks are singled out as the main evaluative means of achieving the educational results of future teachers. As a result of the study, three main educational outcomes in the field of educational activities were developed. To assess the educational results of the field of educational activities, indicators of the achievement of educational results in the preparation of future teachers for educational activities have been developed. The formulation of the educational result allows to determine the target component of the educational process, as well as to select the optimal combination of methodological approaches and means in organizing the conditions for its achievement. An important aspect is the selection of optimal evaluation tools for independent evaluation of educational results.